Exploring Pay Equity: The Role of Public and Employee Stakeholders in Shaping CEO-Worker Pay Ratios - Mohammad Chaidir; Seger Santoso; Farah Qalbia (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This research investigates the impact of stakeholder pressures on executive compensation practices, focusing on the influence of public and employee stakeholders through the disclosure of CEO-worker pay ratios and regulatory frameworks. The primary objective is to analyze how these stakeholders shape corporate governance norms and executive pay policies. Employing a qualitative methodology, this study synthesizes contemporary research on the subject. It reviews strategic organizational responses aimed at enhancing transparency and fairness in executive compensation. Data were gathered from various scholarly articles, regulatory reports, and case studies, providing a comprehensive overview of the current landscape. The Result reveal that the public and employee stakeholders have a substantial influence on CEO compensation policies. According to the study, more pay equity transparency promotes improved stakeholder confidence, corporate accountability, and organizational reputation. It also emphasizes how businesses adjust to legal changes and the wider consequences for corporate social responsibility.